THE ESSENCE AND PURPOSE OF THE TRANSPORT NODES IN THE CONTEXT OF DEVELOPING INTERNATIONAL TRADE AND TRANSPORT STRATEGY OF UKRAINE - Volkanova, N. D. (Science and Transport Progress, 2008)
Ways of improving the efficiency of transport process management at a transport junction are investigated. The methods of introduction of the logistic technologies into the management process at a transport junction are suggested.